Critical inquiry on the use and value of 19th and 20th century travel diaries for environmental history reconstructions in general and South Sinai in specific - Servaes, Caroline D. (2018)
The Sinai Peninsula (Egypt), which connects the African and Eurasian continents, has a rich history. However, the environmental history of this arid to hyper-arid area, which has been very isolated even until recent decades, has not been described yet. In absence of (longterm) quantitative measurements for the area, this thesis explores predominantly 19th and 20th century West-European travel writing as a possible source for environmental history reconstruction. Pre-19th-century, South Sinai attracted mainly pilgrims, who visited what is traditionally believed to be the landscape of the Biblical Exodus; a visit to Mount Sinai, where Moses received the Ten Commandments, and the Monastery of St Katherine formed the climax. In the late 18th- and 19th-century, the area saw an enormous increase in systematic travel writing as a result of European political interest in the strategically positioned Peninsula, growing criticism on the reliability of the Bible, and growing mass-tourism. This has resulted in very abundant but little explored travel writing, in which travellers described their daily life in the desert, the daily weather, the places they visited, their geographical imaginations, and their socio-political and economic interactions. The data extracted from these diaries were extremely rich in detail and highly useful for environmental history reconstruction of South Sinai. Furthermore, they may help understand climatic and environmental trends on local as well as global levels. At this point it is not clear to what extent information from travel writing is interesting for environmental reconstructions of other than arid areas, where the environment and inhabitants are less directly depending on the weather for survival.